2015 23rd Telecommunications Forum Telfor (TELFOR) 2015
DOI: 10.1109/telfor.2015.7377508
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of muscle models for physiologically based intonation modelling

Abstract: Abstract-Prosody is a crucial aspect of the speech signal and its modelling is of great importance for various speech technologies. Intonation models based on physiology rely on an accurate model of muscle activation. Although most of them are based on the spring-damper-mass (SDM) muscle model, the more complex Hill type model offers a more accurate representation of muscle dynamics. In this paper we analyse and compare these two muscle models and discuss the benefits and disadvantages they bring. This researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In the GCR model, the output filters approximate muscle activation. Different models for muscle response are investigated in [9]. Even though previous research [10,11] has shown that higher order systems can improve intonation modelling performance, we use a second-order Spring-Damper-Mass (SDM) muscle model in this work.…”
Section: Muscle Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the GCR model, the output filters approximate muscle activation. Different models for muscle response are investigated in [9]. Even though previous research [10,11] has shown that higher order systems can improve intonation modelling performance, we use a second-order Spring-Damper-Mass (SDM) muscle model in this work.…”
Section: Muscle Modelsmentioning
confidence: 99%
“…This, in turn, allows to express the stability constraint as (7), which can be imposed by using a compressing transformation [5] as sigmoid (8). The cosine of the pole angle can also be transformed to use the whole parameter space by defining c in (9).…”
Section: Muscle Modelsmentioning
confidence: 99%
“…Its transfer function under steady state initial conditions and an impulse driving force is given in (3). To derive its resonant frequency ω 0 (4) we can use the impedance electro-mechanical analogy [1] to draw the equivalent electrical circuit, find its input impedance Z i (jω), and equate its imaginary part to 0 [7]. Unfortunately, there is no straightforward solution for the damping ratio ζ [11].…”
Section: Sdm and Hill Muscle Modelsmentioning
confidence: 99%
“…Recently, we have analysed the two most commonly used muscle models: the 2 nd order SDM model and the 3 rd order Hill type model [7]. Research suggests that the SDM model is too simple to capture the basic mechanics of muscle activation [10].…”
Section: Introductionmentioning
confidence: 99%